Association of body mass index and age as risk factors for post-anesthetic shivering in mastectomy patients under general anesthesia in East Java, Indonesia - Reko Priyonggo; Muhammad Rodli; Suryanto Suryanto; Annes Rindy Permana; Widigdo Rekso Negoro; Sindu Sintara (International Journal of Public Health Science (IJPHS), 2026)
Intraoperative hypothermia and post-anesthetic shivering (PAS) remain frequent complications in oncologic surgery under general anesthesia, yet evidence integrating intraoperative temperature changes with PAS severity in mastectomy patients is limited. This study aimed to evaluate intraoperative temperature profiles, determine the incidence and severity of PAS, and analyze the association between age, body mass index (BMI), and PAS among radical mastectomy patients. A cross-sectional observational study was conducted involving 36 women undergoing radical mastectomy with endotracheal general anesthesia. Core temperature was measured at 30 and 60 minutes intraoperatively, and PAS was assessed using the bedside shivering assessment scale (BSAS) upon admission to the recovery room. Moderate intraoperative hypothermia was observed in 72.2% of patients at 60 minutes, while PAS occurred in 30.6% of cases. Significant associations were identified between PAS and BMI (p = 0.001), as well as age (p = 0.026). Moderate-to-severe shivering (BSAS scores 2-3) was more frequently observed among underweight and elderly patients. This study provides novel evidence by linking intraoperative hypothermia patterns with PAS severity using BSAS in mastectomy patients. Clinically, the findings support structured perioperative temperature monitoring and the implementation of risk-based warming protocols, particularly for patients with low BMI and advanced age.